The means of verbalizing will expression in a literary text as the dominants of the author’s idiostyle (exemplified by I. Bachmann’s novel "Malina") - Tolparova, Dzerassa Valerievna (Филология: научные исследования, 2024)
The imperative mood expresses the will of the communicative act’s producer and requires a verbal or non-verbal reaction from the recipient. This article is devoted to the study of ways to implement voluntariness in the language of a literary work. The material for this work is the novel "Malina" by the Austrian writer Ingeborg Bachmann. The object of the study is the category of motivation as a way of expressing the will of the producer. The article examines the grammatical and lexical means of verbalizing will that are presented in the analyzed novel by a wide range of forms of explicit and implicit expression of motivation. Special attention is paid to the verb form of the 2nd person singular which forms the core of the imperative mood category and takes priority by the highest frequency of use in I. Bachman's idiolect. The following methods were used in the course of the study: descriptive method, structural method, component analysis method, logical comparison method, statistical analysis method. The scientific novelty of the study lies in the fact that for the first time an attempt was made to establish a correlation between the degree of use frequency of will manifesting means of the writer, characterized by the desire to change the surrounding reality. The analysis of empirical material revealed the tendency for Ingeborg Bachmann to use most of the methods of verbalizing the imperative mood available in the German language. The main conclusion of the study is that indirect ways of expressing will (as well as direct ones) can be represented in artistic discourse by both grammatical and lexical means which are part of imperative structures with modal verbs, as well as elliptical constructions and can be narrative or interrogative sentences from the standpoint of communicative purpose.